Alternative electron donors to photosystem II play an important role in the reduction of the electron transport chain in heat-treated barley leaves - Tóth Szilvia Zita (Acta biologica Szegediensis, 2005)
Electron donation to TyrZ in heat-inactivated photosystem II (PSII) reaction centers by alternative donors was evaluated. Chl a fluorescence transients indicate that in the 0.1-3 ms range (K-step) only one electron is available, but that in the 0.2-2 s range accumulation of QA- took place that coincided with the re-reduction of plastocyanin PC+ and P700+. Using Chl a fluorescence emission induced by short repetitive pulses and simultaneous 820 nm transmission and Chl a fluorescence transient measurements we show that electron donation to photosystem II takes place with a halftime of ~10 ms. There is a large pool of such alternative donors and they significantly contribute to the reduction of the linear electron transport chain since inhibition of PS II by DCMU prevented the re-reduction of PC+ and P700+.